Haemodynamic effects of hypothalamic disconnection in anaesthetized rats - De Almeida Colombari, Débora Simões [UNESP]; Portelinha, Luciane Schadeck [UNESP]; Campos Jr., Ruy Ribeiro [UNESP]; Lopes, Oswaldo Ubríaco [UNESP] (Elsevier, 2002)
The aim of the present study was to analyse the haemodynamic effects induced by the hypothalamic disconnection (HD) caudal or rostral to the paraventricular nucleus of the hypothalamus (PVN). Mean arterial pressure (MAP), hindlimb, renal and mesenteric blood flow and vascular conductance (HVC, RVC and MVC, respectively) were measured in urethane (1.2 g/kg, i.v.) anesthetized rats for 60 min after disconnection. HD caudal to the PVN was performed with a double-edged microknife of bayonet shape (R=1 mm, H=2 mm) stereotaxically placed, lowered 2.8 mm caudal to the bregma along the midline. The cut was achieved by rotating the microknife 90° right and 90° left. HD rostral to the PVN was performed with the knife placed 0.8 mm caudal to the bregma. Thirty minutes after the hypothalamic disconnection caudal (HD-C), a decrease in MAP was observed (-14±3 mm Hg), reaching a 60-min decrease of 30±3 mm Hg. Hindlimb conductance increased 10 min after HD (156±14%) and remained elevated throughout the experimental period. On the contrary, we observed a transitory renal vasoconstriction (82±9%, ≤20 min) and a late mesenteric vasodilation, starting at 30 min (108±4%) and reaching 138±6% at 60 min. In rats with HD rostral to the PVN, we only observed minor changes in the cardiovascular parameters. In the MAP, there was a slight decrease 60 min after the hypothalamic disconnection rostral (HD-R) (-9±4 mm Hg). There were no significant changes in HVC. RVC and MVC were increased 60 min after the HD-R (116±12% and 124±11%, respectively). These results suggest that vasodilation in the hindlimb and in the mesenteric bed could contribute to the observed decrease in MAP in HD caudal to PVN rats. © 2002 Elsevier Science B.V. All rights reserved.
Keywords: Blood flow; Blood pressure; Hypothalamus; Knife-cut; Paraventricular nucleus; animal experiment; animal tissue; blood flow; brain blood vessel; conductance; conference paper; controlled study; hemodynamics; hindlimb; hypothalamus; kidney; male; mean arterial pressure; mesentery; nonhuman; priority journal; rat; thalamus midline nucleus; vasoconstriction; vasodilatation; Animals; Blood Pressure; Denervation; Hemodynamic Processes; Hindlimb; Male; Paraventricular Hypothalamic Nucleus; Rats; Rats, Wistar; Regional Blood Flow; Renal Circulation; Splanchnic Circulation; Vasoconstriction; Vasodilation